2007
DOI: 10.1021/jp067009t
|View full text |Cite
|
Sign up to set email alerts
|

Supercapacitors from Activated Carbon Derived from Banana Fibers

Abstract: Carbon materials were synthesized from banana fibers by treating the fibers with pore-forming substances such as ZnCl 2 and KOH with an intention to improve the surface area and their electrochemical performance as electrical double-layer capacitor electrodes. The performance of these materials was studied in a neutral electrolyte for the first time. There has been a substantive increase in the specific surface area of the treated carbon material because of the effective pore generations. The structural and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
244
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 553 publications
(256 citation statements)
references
References 25 publications
9
244
1
2
Order By: Relevance
“…As a result of an increase in temperature, new pores are created. In addition, there is a stable increase in both the surface area and the pore volume [24]. The SEM examinations, thus reveal that the cellulose structure decreases with increasing the firing temperature.…”
Section: High Resolution Scanning Electron Microscopy (Hr-sem) Studiesmentioning
confidence: 83%
See 1 more Smart Citation
“…As a result of an increase in temperature, new pores are created. In addition, there is a stable increase in both the surface area and the pore volume [24]. The SEM examinations, thus reveal that the cellulose structure decreases with increasing the firing temperature.…”
Section: High Resolution Scanning Electron Microscopy (Hr-sem) Studiesmentioning
confidence: 83%
“…A polyvinyl alcohol (PVA) and phosphoric acid (H 3 PO 4 ) polymer gel electrolyte was prepared as described in the literature reports and functioned as both the electrolyte and separator [24]. Usually, in industrially produced supercapacitors, aqueous solution of alkali (decomposition voltage of 1.23 V and electrical conductivity of 1.0 S/cm) or organic electrolytes (decomposition voltage of 2.7 V and electrical conductivity of 0.01 S/cm) are used.…”
Section: Device Fabrication Of Awnp 800mentioning
confidence: 99%
“…Table 2 compares the BET surface areas of activated carbon obtained in the present study with those obtained using different feedstocks/activating reagents reported in the literature, with the present study showing the highest BET surface area of 2425 m 2 /g. It is generally believed that the KOH activation process of any carbon material enhances the pore structure and morphology with a substantial increase in specific surface area [14]. [18] -614 Orange peel [19] CO 2 618 Glucose [20] KOH 1197 Palm date seed [21] NaOH 1282 Desert shrub [22] ZnCl 2 1296 Rice husk [23] H 3 PO 4 1498 Hazelnut shell [24] KOH 1700 Glucose [25] KOH 1704 Sucrose [26] H 3 PO 4 2120 Glucose [26] NaOH 2129 Starch [27] KOH 2190 Rye straw [28] KOH 2200 Eucalyptus sawdust [29] KOH 2252 Corncobs [30] KOH 2300 Hemp bast fiber (this study) KOH 2425 Figure 1 provides the N 2 adsorption-desorption isotherms at −196 • C and pore size distributions of HAC, where HACs were prepared using different biochar-to-KOH ratios at a synthesis temperature of 390 • C. All the adsorption-desorption isotherms exhibit a type IV isotherm with a type IV hysteresis loop (according to IUPAC classification) in the relative pressure range from 0.4 to 1.0.…”
Section: Resultsmentioning
confidence: 99%
“…Organic groups with oxygen, typically, phenols, carbonyls, lactones, quinone and quinone-like structures are expected to form on the surface during the thermal treatment of the biomass precursors and may appear at the edge carbon atoms as indicated by Subramanian et al [36]. This fact may also be applied to JFSC samples and the effect or mechanism of action of these organics on the electroactivity of the carbon samples may be complex and forms an exclusive research object.…”
Section: Fig 4 Ft-ir Of Jsfc Powdermentioning
confidence: 99%
“…Survey of recent research reports shows that carbon materials derived from biomass has the potential of being utilized as electrode materials in electrochemical capacitors [33][34][35][36][37][38][39][40]. Hence, the purpose of this study is to examine the feasibility of obtaining carbon from a common domestic vegetable waste viz., the Jack Fruit Seeds (JFS) and to completely evaluate the applicability of the obtained carbon as an electrode material for electrochemical capacitor (pseudocapacitors) in acid as well as neutral medium.…”
Section: Introductionmentioning
confidence: 99%